2019
DOI: 10.1002/app.48268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vinyl acetate content on the photovoltaic‐encapsulation performance of ethylene vinyl acetate under accelerated ultra‐violet aging

Abstract: The vinyl acetate (VA) content in ethylene vinyl acetate (EVA) can significantly affect its performance as an encapsulant in photovoltaic modules under field conditions. EVA films of varying VA content (18, 24, 33, and 40%) have been prepared using twin screw extruder with the necessary additives and subsequently cured at 150 C. All the EVA films have been subjected to UV radiation at a wavelength of 340 nm for 1000 and 2000 h to simulate accelerated field aging. The effects of accelerated aging on the gel con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Therefore, overlying layers are required to be highly transparent for ultraviolet and visible light. Preliminary tests on 3M-F375PMA film with a thickness of 0.50 mm show a transmittance of T > 85% between 1000 and 515 nm, and a UV-cutoff at 315 nm ( Figure S5 in the Supplementary Materials), which is comparable to poly(ethylene-co-vinyl acetate) (EVA) used as photovoltaic encapsulants [58].…”
Section: Ambient-temperature Healing Application: Encapsulant In Photmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, overlying layers are required to be highly transparent for ultraviolet and visible light. Preliminary tests on 3M-F375PMA film with a thickness of 0.50 mm show a transmittance of T > 85% between 1000 and 515 nm, and a UV-cutoff at 315 nm ( Figure S5 in the Supplementary Materials), which is comparable to poly(ethylene-co-vinyl acetate) (EVA) used as photovoltaic encapsulants [58].…”
Section: Ambient-temperature Healing Application: Encapsulant In Photmentioning
confidence: 96%
“…Due to mismatching thermal expansion coefficients of the different layers, thermal cycling can lead to thermal stress [59]. Therefore, conventional encapsulant layers, such as EVA and polyolefin elastomer (POE) [58], are susceptible to the formation of micro-defects, which may impair solar panel efficiency if they grow into larger defects. Introducing self-healing properties into the encapsulant material can help prevent crack growth in the encapsulant layer through regular healing of newly formed micro-defects.…”
Section: Ambient-temperature Healing Application: Encapsulant In Photmentioning
confidence: 99%
“…Copolymers of ethylene and vinyl acetate (EVA) are popularly used as encapsulants in solar PV modules. Accelerated weathering studies on several different EVA copolymers found those with 18–33% by weight in copolymer vinyl acetate to be the most stable to solar UV radiation [ 481 ]. The encapsulant degradation of EVA by solar UV radiation, as assessed by FTIR, was found to be inhomogeneous, suggesting that intrusion of oxygen and moisture from the edges into the interior of laminates governed their degradation process [ 482 ].…”
Section: Materials Damagementioning
confidence: 99%
“…The presence of vinyl acetate moieties in EVA induced a different ability of the material to crystallize. Ethylene segments in vinyl acetate moieties have the tendency to form smaller and less perfect crystals, which melt at lower temperatures compared to the polyethylene units [ 18 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the exposure in the test chamber at 60 °C, smaller crystals with thinner lamellae can melt and crystallize again to form more perfect crystals with thicker lamellae, which melt at higher temperatures [ 27 , 37 ]. Additionally, in the last two steps of the UV test, it is possible to notice a shift of the melting temperature visible in the second heating run of the DSC measurement from 66 °C to 68 °C and finally to 86 °C, which is an indicator for the occurrence of deacetylation reaction [ 18 , 39 ]. Signs of chemo-crystallization are noticeable also when looking at the cooling curve of the thermogram ( Figure 8 d) because the crystallization peak is shifted to much higher temperatures and the temperature range in which the crystallization process takes place is enlarged.…”
Section: Resultsmentioning
confidence: 99%